PEMBUATAN SISTEM ROBOTIKA SEBAGAI IMPLEMENTASI PERGERAKAN KAMERA SECARA AUTONOMOUS - Putra, Dimas Kusuma; Martinus, .; Yahya TP, Ahmad (Jurnal Ilmiah Teknik Mesin FEMA, 2014)
Automation systems are a manifestation of the concept of science that led to development of nowadays technology. In general automation is concept of human science that is used to run a process where there is no longer direct human intervention ranging from the beginning of the process until completion. This research is intended to create a automated a robotic system camera pan and tilt movements with a view to be implemented into a variety of forms of applications, such as KAP (Kite Aerial Photography), security camera, stealth cam, camera traps and etc. This research uses some mechanicsm of rigging as a medium for system the camera Arduino microcontroller is used as the controller of the controlling the camera movement. The system of controlled the movement of the camera by using time delay. The results showed that the robotics system of this research has succeeded in making a camera capable of autonomous moving to state time delay. Keywords: Microcontroller, Robotics Systems, Camera Movement.